Grundtvigs prædiken 2. s.e. trin. 1840 - Holm, Jette (Grundtvig-Studier, 1996)
Grundtvig’s Sermon on the Second Sunday after Trinity, 1840. By Jette Holm In 1983 the comprehensive edition of Grundtvig’s sermons during the 1820s and 1830s was completed. A group of editors, headed by Christian Thodberg and with Jette Holm, Leif Kallesen, Elisabeth Albinus Glenthøj and Johannes Glenthøj and others as participants, have undertaken the task of transcribing the sermons from the 1840s. An example of these sermons, held in connection with the coronation of Christian the Eighth, is reprinted here. The sermon deals with Grundtvig’s reflections on the relation between the national spirit and the Holy Spirit.